Character and Family Violence Prevention Education in Madrasah Tsanawiyah: Anti-Parricide Learning Model - Aang Kunaepi; Akhmad Yusuf Isnan Setiawan; Nasikhin; Abdulraya Panaemalae (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the potential, strategies, and implications of anti-parricide education in Islamic Junior High Schools (MTs). Using a qualitative approach with a phenomenological design and the Miles and Huberman data analysis model, the study was conducted at MTs Hasyim Asy'ari Bawang, Batang, through 24-hour observations, in-depth interviews, and document analysis such as syllabi, guidance and counseling modules, and student behavior records. The main findings indicate that the potential for parricide is triggered by three indicators: student aggressive behavior, untreated mental health disorders, and unstable or violent family environments. The school responded by integrating character values ​​into the curriculum, strengthening guidance and counseling services, and creating a religious madrasa environment. This aligns with the teachings of Al-Ghazali's theory of moral education. However, challenges such as domestic violence, limited teacher competency, and the negative influence of social media hamper the effectiveness of these strategies. The theoretical contribution of this research lies in the development of a contextual anti-parricide education model based on madrasahs, while its practical contribution is in the form of policy recommendations for strengthening character education and early prevention systems involving synergy between schools, families, and communities.